The Synthesis and Performance of Sodium Methyl Ester Sulfonate for Enhanced Oil Recovery - Elraies, Khaled A (Taylor & Francis Group, LLC, 2010)
Due to the high cost of surfactant production caused by petrochemical feedstocks, much attention has been given to nonedible vegetable oils as an alternative source of feedstock. A new nonedible oil-derived surfactant based on the Jatropha plant is synthesized. A single-step route was used for synthesizing sodium methyl ester sulfonate (SMES) for enhanced oil recovery application. The performance of the resultant surfactant was studied by measuring the interfacial tension between the surfactant solution and crude oil and its thermal stability at reservoir temperature. The SMES showed a good surface activity, reducing the interfacial tension between the surfactant solution and crude oil from 18.4 to 3.92 mN/m. The thermal analysis of SMES indicates that 26.1% weight loss was observed from 70ıC to 500ıC. The advantage of the new SMES is the low cost of production, which makes it a promising surfactant for enhanced oil recovery application and other uses